The Idea of Innovation Behavior in Present Day Economy - E. A. Danilenko; V. N. Rogozhnikova (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
Fast development of innovation and energetic introduction of new technologies in everyday life exercise a great impact on shaping behavior patters. A prime goal of innovation development is to stimulate people’s abilities and competences that could allow them not only to adapt to constant changes in the world but also to initiate such changes. As a result, a notion of a new type of man’s behavior is being devised in today’s economics, i.e. innovation one. The article provides characteristic of key features of this phenomenon. The goals of the research is to identify sources of innovation behavior in economy and approaches to its investigation; to show factors stipulating individual’s inclination to innovation behavior; to characterize peculiarities of innovation behavior in production and consumption. To attain the mentioned goals the authors use methods of description and comparative analysis, inductive and genetic approaches. The authors came to the conclusion about dubious nature of innovation behavior and domination of individual and personality but not collective conditionality in it. At the same time changes in behavior patters are typical not only of individuals directly participating in production and new technology introduction, but also of consumers of the latter. Finally, the authors provide a summarized definition of innovation behavior in view of economic theory.